Hudson's Bay, or, Everyday life in the wilds of North America during six years' residence in the territories of the Hon. Hudson's Bay Company [electronic resource] - Ballantyne, R. M. (Robert Michael), 1825-1894. (Boston : Phillips, Sampson, 1859)
Electronic reproduction. Mode of access: Internet. 44